Evaluating Welfare Reform in the United States - Blank, Rebecca M (Journal of Economic Literature, 2002)
This paper reviews the economics literature on welfare reform over the 1990s. A brief summary of the policy changes over this period is followed by a discussion of the methodological techniques utilized to analyze the effects of these changes on outcomes. The paper then critically reviews the econometric and experimental literature on caseload changes, labor force changes, poverty and income changes, and family formation changes. A growing body of evidence suggests that the recent policy changes have influenced economic behavior and well-being in a variety of ways. One particular set of "new-style" welfare programs seems to show especially promising results, with significantly increased work and earnings and reduced poverty.